The Site Where Newly Synthesized ATP Is Necessary for Tension Development in α-Toxin Permeabilized Preparations of Rat Proximal Colon - Tadayoshi Takeuchi; Akikazu Fujita; Masahiko Kushida; Fumiaki Hata (Elsevier, 2003)
Since it was suggested in our previous study that ATP newly synthesized from ADP and phosphocreatine (PCr) by creatine kinase had an important role in Ca2+-induced phasic contraction in α-toxin permeabilized smooth muscle of rat proximal colon, we studied the role of newly synthesized ATP on myosin ATPase activity, by assessing a rate of force development as an index of myosin ATPase activity. The α-toxin-permeabilized preparations were thiophosphorylated by treatment with ATPγS. After the thiophosphorylation, the contraction induced by ATP plus PCr in the absence of Ca2+ reached the maximum at 30 s. When PCr was omitted from the bathing solution, the initial rate of the contraction was significantly slower, while the level of myosin light chain thiophosphorylation remained unchanged. An inhibitor of creatine kinase slowed the initial contractile rate to a rate similar to that induced by ATP alone. ADPβS had no effect on ATP plus PCr-induced contraction, suggesting that accumulation of ADP does not affect the initial rate of the contraction. PCr alone did not contract the thiophosphorylated-preparations. However, in the presence of ADP, PCr induced contraction at the initial rate which was slower than that induced by ATP plus PCr. These results indicate that newly synthesized ATP together with preexisting ATP is utilized as a substrate for myosin ATPase.